Penggunaan Model Set Covering Problem dalam Penentuan Lokasi dan Jumlah Pos Pemadam Kebakaran - Puspitasari, Yesi; Sari, Lisma Dian Kartika; Indayani, Darsih (Universitas Dr. Soetomo, 2020)
AbstractOver the past five years, the incidence of fires at the Situbondo Regency has increased. For the following years, the Situbondo district government plans to add new fire stations to reach areas that have not been or are difficult to reach by fire and rescue unit personnel. In the construction plan for a new fire station, we need to construct a model that can determine where and how many new fire stations. This research aims to determine the optimal location and number of fire stations taking into account dispatch time, construction cost, and fire toll in Situbondo district using the set covering problem model. Furthermore, we find the solution of the model by using the branch and bound method compiled from the GAMS optimization software. The optimal solution of the set covering problem model which minimizes the opening cost of the fire station as the objective function is, and each equal to 1 with Z equal to 6. Based on the result, the optimal location of the fire station in Situbondo district is in the sub-districts of Banyuglugur, Mlandingan, Bungatan, Panji, Kapongan, and Arjasa, each with a type C station. Currently, Situbondo district fire stations are located in Panji (type A), Asembagus (type C), and Besuki (type C) sub-districts. The costs incurred for the construction of the three fire stations are 7. The total cost of new fire station construction in the optimization model is less than the cost issued at this time. Keywords: set covering problem, branch and bound, fire station location, GAMS. AbstrakSelama lima tahun terakhir, kejadian kebakaran di Kabupaten Situbondo meningkat. Beberapa tahun kedepan, Pemerintah Kabupaten Situbondo berencana akan menambah pos baru untuk menjangkau daerah-daerah yang selama ini belum atau sulit dijangkau oleh personil UPT Pemadam Kebakaran dan Penyelamatan. Dalam rencana pembangunan pos pemadam kebakaran baru dibutuhkan metode yang tepat untuk menentukan dimana dan jumlah lokasi pos pemadam kebakaran baru yang strategis. Penelitian ini bertujuan untuk menentukan lokasi dan jumlah pos pemadam kebakaran yang optimal dengan mempertimbangkan waktu tempuh, biaya pembangunan, dan rekam jejak terjadinya kebakaran di Kabupaten Situbondo menggunakan model set-covering problem. Selanjutnya, model tersebut diselesaikan menggunakan metode branch and bound dengan menggunakan software optimasi GAMS. Penyelesaian model optimasi Set Covering Problem yang meminimalkan fungsi objektif biaya pembukaan pos pemadam kebakaran adalah , dan masing-masing sama dengan 1 dengan nilai Z adalah 6. Berdasarkan hasil tersebut lokasi pos pemadam kebakaran yang optimal di Kabupaten Situbondo adalah di Kecamatan Banyuglugur, Mlandingan, Bungatan, Panji, Kapongan, dan Arjasa yang masing-masing dengan tipe pos pemadam kebakaran C. Saat ini lokasi pos pemadam kebakaran yang dimiliki oleh UPT Pemadam Kebakaran dan Penyelamatan Kabupaten Situbondo terletak di 3 lokasi, yaitu Kecamatan Panji (tipe A), Kecamatan Asembagus (tipe C), dan Kecamatan Besuki (tipe C), maka biaya yang dikeluarkan untuk pembangunan ketiga pos pemadam kebakaran tersebut adalah 7. Total biaya pembangunan pos pemadam kebakaran baru pada model optimasi lebih kecil daripada biaya yang dikeluarkan saat ini. Kata Kunci: set covering problem, branch and bound, lokasi pos pemadam kebakaran, GAMS.